Análise de agrupamentos para o reconhecimento de padrões de infestação de aracnídeos em zonas urbanas - Biazi, Angelo Henrique [UNESP] (2015)
Arachnids have been successful along the evolutionary process thanks to their high adaptability. Within this group, spiders and scorpions are widely distributed on the planet and may affect human health. In order to evaluate the infestation problems caused by these animals, it is necessary to use statistical tools that can assess the factors that favor or perpetuate their appearance, presence and proliferation. Thus, this work aims to present cluster analysis in order to determine infestation patterns, allowing seemingly distinct sites to be grouped into similar clusters, which can benefit health policies. The 25 geographic collection sites used for sampling were divided into six groups with different characteristics, among which three were formed by a single collection point (outliers). The groups obtained showed a relationship with the environmental characteristics of the sites, indicating that the distribution of arachnid families in the different urban gradients is influenced by environmental conditions. Therefore, the occupation of urbanized areas by venomous arachnids becomes a problem for public health, requiring epidemiological control policies through monitoring and mapping of risk areas, which can be better assessed with the use of cluster analysis